The resistance of Salmonella spp. isolates from Alabio duck against several antibiotics - ., Istiana (Indonesian Journal of Animal and Veterinary Sciences, 1998)
A total of 172 isolates of Salmonella spp. consisted of S. typhimurium (70), S. Radar (52), S. senftenberg (25), S. Virchow (14), and S. amsterdam (11) from Alabio duck hatcheries in the District of Hulu Sungai Utara, South Kalimantan, were examined their resistencies against seven kinds of antibiotics, consisted of chloramphenicol, neomycin, trimethoprim, streptomycin, tetracycline, ampicillin, and polymixin B, by using agar disc diffusion method. The results showed that 70 isolates of S. typhimurium were resistant against six kinds of antibiotics with various percentages, that is chlorampenicol 5 .7%, neomycin 12 .8%, trimethoprim 7.1 %, streptomycin 8 .6%, tetracycline 11 .4%, and the highest against ampicillin 30 %. Ofthe 52 S. hadar isolates showed that all ofthem were resistent against 6 kinds of antibiotics, that is chloramphenicol 1 .9%, neomycin 7.7%, trimethoprim 5.8%, streptomycin 48 .0%, tetracycline 48.0%, and polymixin B 3.8%. Futhermore S. senftenberg (25 isolates) were resistent against three kinds of antibiotics, that is neomycin 12%, streptomycin 20%, and tetracyclines 16%. Meanwhile S. virchow (14 isolates), were resistant against two kinds of antibiotics namely streptomycin 7.1% and tetracylines 14.3%. Whereas S. amsterdam (11 isolates) were resistant against four kinds of antibiotics, that is neomycin 45 .5%, streptomycin 18 .2%, tetracycline 18 .2%, and ampicillin 9.10%. Â  Key words: Resistance, Salmonella spp., Alabio ducks, antibiotics